Evaluation of Islamic Education Curriculum Policy in Indonesia - Choirul Mahfud (Universitas PGRI Madiun, 2019)
The most sensitive thing in the context of Islamic education policy in Indonesia is the change of curriculum. The Islamic education curriculum cannot be separated from the national education curriculum, because Islamic education is a national education subsystem. If the national education curriculum changes, then the Islamic education curriculum also changes. In this context, as adagium